MUTYH c.933+3A>C, associated with a severely impaired gene expression, is the first Italian founder mutation in MUTYH‐Associated Polyposis. Issue 5 (28th August 2012) - Pin, Elisa; Pastrello, Chiara; Tricarico, Rossella; Papi, Laura; Quaia, Michele; Fornasarig, Mara; Carnevali, Ileana; Oliani, Cristina; Fornasin, Alessio; Agostini, Marco; Maestro, Roberta; Barana, Daniela; et al.
Abstract MUTYH variants are differently distributed in geographical areas of the world. In MUTYH‐associated polyposis (MAP) patients from North‐Eastern Italy, c.933+3A>C (IVS10+3A>C), a transversion causing an aberrant splicing process, accounts for nearly 1/5 of all mutations. The aim of this study was to verify whether its high frequency in North‐Eastern Italy is due to a founder effect and to clarify its impact on MUTYH transcripts and protein. Haplotype analysis and age estimate performed on members of eleven Italian MAP families and cancer‐free controls provided evidence that c.933+3A>C is a founder mutation originated about 83 generations ago. In addition, the Italian haplotype associated with the c.933+3A>C was also found in German families segregating the same mutation, indicating it had a common origin in Western Europe. Altogether c.933+3A>C and the two common Caucasian mutations p.Tyr179Cys and p.Gly396Asp represent about 60% of MUTYH alterations in MAP patients from North‐Eastern Italy, suggesting the opportunity to perform targeted molecular screening for these variants in the diagnostic setting. Expression analyses performed on lymphoblastoid cell lines supported the notion that MUTYH c.933+3A>C alters splicing causing the synthesis of a non functional protein. However, some primary transcripts escape aberrant splicing, producing traces of full‐length transcript and wild‐type protein in a homozygote; this is in agreement with clinical findings that suggest a relatively mild phenotypic effect for this mutation. Overall, these data, that demonstrate a founder effect and further elucidate the splicing alterations caused by the MUTYH c.933+3A>C mutation, have important implications for genetic counseling and molecular diagnosis of MAP.